Numerical simulation for solution of SEIR models by meshless and finite difference methods. (December 2020) - Asif, Muhammad; Ali Khan, Zar; Haider, Nadeem; Al-Mdallal, Qasem
Abstract: The transmission of influenza has been explained by analyzing a diffusive epidemic model. The Operating splitting based on finite difference (OSBFD), explicit formula based on meshless method (EFBMM), Operator splitting based on meshless method (OSBMM) are applied to obtain numerical solutions of equations under varied initial distribution of dense population. The specific role of diffusion and distribution has been accentuated in spread of ailment. It is also presented that how the transmission of disease is specifically reduced by the medicative and non-medicative innovations. The numerical solutions involved in stability of all the equilibria are also stated.